2020
DOI: 10.4314/ahs.v20i2.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukins (IL-2, IL-15, IL-18) on receptors activation and cytotoxic activity of natural killer cells in breast cancer cell

Abstract: Introduction: Breast cancer is one of the leading cause of cancer deaths in women. Metastasis in BC is caused by immuno- surveillance deficiency, such NK cell maturation, low NK activity and decreasing cytotoxicity. This study was performed to improve activating receptors and cytotoxicity of NK cells using interleukins (ILs). Methods: Human recombinant IL-2, -15, and -18 were used to induce NK cells. We measured the activating and inhibiting receptors, proliferation activity of NK cells, and the cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 63 publications
1
29
1
Order By: Relevance
“…Triggered NK cells can kill cancerous cells by direct cell cytotoxicity and/or generation of pro-inflammatory cytokines. In addition to the releases of perforin and granzymes for tumor cell elimination, NK cells exert antibody-dependent cellular cytotoxicity (ADCC) by the membrane receptor CD16 or apoptotic axis intermediated by Fas ligand (FasL) or TNF-related apoptosis-inducing ligand (TRAIL) ( Figure 1 ) ( 12 , 13 ). Furthermore, modulation of anti-tumor immune responses by NK cells leads to secretion of cytokines and chemokines including interferon-γ (IFN-γ) and granulocyte-macrophage colony-stimulating factor (GM-CSF) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Triggered NK cells can kill cancerous cells by direct cell cytotoxicity and/or generation of pro-inflammatory cytokines. In addition to the releases of perforin and granzymes for tumor cell elimination, NK cells exert antibody-dependent cellular cytotoxicity (ADCC) by the membrane receptor CD16 or apoptotic axis intermediated by Fas ligand (FasL) or TNF-related apoptosis-inducing ligand (TRAIL) ( Figure 1 ) ( 12 , 13 ). Furthermore, modulation of anti-tumor immune responses by NK cells leads to secretion of cytokines and chemokines including interferon-γ (IFN-γ) and granulocyte-macrophage colony-stimulating factor (GM-CSF) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…IL-15 is essential for NK cell survival, differentiation, and proliferation (Anton et al 2015). Improving NK cells cytotoxicity used ILs (IL15, IL18), the result showed that ILs increased TNFα, IFNγ secretion by NK cells (Widowati et al 2020) IL15 induces optimal production of IFN-γ from NK cells, subsequently induce apoptosis of the NK cells toward cancer cells (Ross and Caligiuri 1997;Widowati et al 2020). The human MHC class I-negative of small cell lung cancer cell line (N592) genetically engineered to secrete IL-15, N592/IL-15, showed a reduced tumor growth rate (Orengo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This result was validated previous research that activated NK cells released higher levels of IFN-γ, TNF-α, Prf1, and GzmB compared to non-induced NK cells. IL2, IL15, and IL18 increased the secretion of IFN-γ, TNF-α, Prf1, and GzmB by coculture cells (Widowati et al 2020). IL15 in NK cell controls as well survival of mature NK cells in the periphery (Marçais et al 2013;Widowati et al 2020), mediated by up-regulation of anti-apoptotic bcl2 family members and down regulation of apoptotic (Marçais et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations